Formability, Microstructure and Mechanical Properties of Flow-Formed 17-4 PH Stainless Steel - Maj, P.; Adamczyk-Cieslak, B.; Lewczuk, M.; Mizera, J.; Kut, S.; Mrugala, T. (Journal of materials engineering and performance, 2018)
The subject of the research that has been conducted in this paper was to analyze precipitation-hardened martensitic stainless steel 17-4 PH after flow forming with four different strains and subsequent standard heat treatment. Four cylinders were obtained with a 16, 30, 48 and 68% reduction in thickness, respectively. The samples were analyzed in terms of their mechanical properties and microstructural changes before and after the heat treatment. The results showed that a higher strain resulted in an overall higher strength (up to 1200 MPa UTS) and refinement of the structure, although at a cost of the elongation. High deformation influenced the precipitation process, and the ratio of the grain boundaries significantly increased. Nonetheless, comparing the obtained results with other similar research, it seems that the formation of nano-precipitates of Cu is the key-strengthening mechanism. Strain hardening contributes to an increase in the strength of the steel, although the effect decreases after heat treatment. The relatively small values of residual stress in the steel, especially after the heat treatment, confirmed these claims. Overall, flow forming allowed high deformations of the 17-4 PH steel to be obtained although it did not significantly change the mechanical properties of the material due to the dominant precipitation hardening mechanism.